2018
DOI: 10.1016/j.celrep.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Although Abundant in Tumor Tissue, Mast Cells Have No Effect on Immunological Micro-milieu or Growth of HPV-Induced or Transplanted Tumors

Abstract: High numbers of mast cells populate the stroma of many types of neoplasms, including human papilloma virus-induced benign and malignant tumors in man and mouse. Equipped with numerous pattern recognition receptors and capable of executing important pro-inflammatory responses, mast cells are considered innate sentinels that significantly impact tumor biology. Mast cells were reported to promote human papilloma virus (HPV)-induced epithelial hyperproliferation and neo-angiogenesis in an HPV-driven mouse model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Mcpt5-Cre R26 DTA/DTA mice featured virtually complete absence of CTMCs in peritoneal cavity and skin without alteration of other hematopoietic cell subsets in peritoneum, skin, spleen, bone marrow, or blood as determined by flow cytometry and histology (Figure S1 in Supplementary Material). We had earlier shown highly efficient depletion of skin MCs on formalin-fixed, Giemsa-stained sections (47). As mucosal MCs of the intestinal tract can be metachromatically stained using special fixation procedures like Carnoy fixation but not after formalin fixation, we now performed additional Giemsa staining of Carnoy-fixed skin to exclude the presence of skin MC populations that fail to stain with conventional protocols (Figure S1 in Supplementary Material) and confirmed near complete absence of MCs in the skin of Mcpt5-Cre R26 DTA/DTA mice.…”
Section: Resultsmentioning
confidence: 99%
“…Mcpt5-Cre R26 DTA/DTA mice featured virtually complete absence of CTMCs in peritoneal cavity and skin without alteration of other hematopoietic cell subsets in peritoneum, skin, spleen, bone marrow, or blood as determined by flow cytometry and histology (Figure S1 in Supplementary Material). We had earlier shown highly efficient depletion of skin MCs on formalin-fixed, Giemsa-stained sections (47). As mucosal MCs of the intestinal tract can be metachromatically stained using special fixation procedures like Carnoy fixation but not after formalin fixation, we now performed additional Giemsa staining of Carnoy-fixed skin to exclude the presence of skin MC populations that fail to stain with conventional protocols (Figure S1 in Supplementary Material) and confirmed near complete absence of MCs in the skin of Mcpt5-Cre R26 DTA/DTA mice.…”
Section: Resultsmentioning
confidence: 99%
“…As MCs can infiltrate the surrounding stroma of certain tumors, [69][70][71] many studies performed in human and mice focused on the role of MCs in tumor immunology. Whereas some studies revealed no effect of MCs on tumor progression, [72][73][74] others reported a positive role of MCs and pointed out MCs as responsible for tumor growth inhibition in mice, or related the presence of MCs to a good prognosis for the patient. 75,76,[76][77][78] A positive influence of MCs can rely on their ability of the release of antitumorigenic molecules such as tumor necrosis factorα, IL-9, or IL-6.…”
Section: Que S Ti Onab Le Role Of Ma S T Cell S In Tumor Immunologymentioning
confidence: 99%
“…However, when the experiment was repeated in the KITindependent Mcpt5-Cre R26 DTA model of MC deficiency, neoplastic growth and tumor angiogenesis were not impaired compared with that seen in control mice, despite the absence of MCs. 58 Likewise, HPV-induced epidermal neoplasia was unaffected by selective inactivation of the Vegfa gene in MCs. 58 Also, in the Cpa3 Cre/1 model of MC deficiency, absence of MCs had no effect on epidermal tumor growth, which was in this case induced chemically.…”
Section: Role Of Mcs In Patients With Cancermentioning
confidence: 99%
“…48 Mcpt5-Cre bacterial artificial chromosome transgenic mice express Cre in CTMCs but not in MMCs, allowing for efficient selective gene inactivation in CTMCs. 53,[57][58][59] In addition, a small fraction of NK cells expressed Cre. 59 The line was crossed to R26 DTA mice, 60 in which Cre-mediated excision of a stop results in suicidal expression of diphtheria toxin.…”
Section: How To Study the Contribution Of Mcs To Diseasementioning
confidence: 99%
See 1 more Smart Citation